2016
DOI: 10.1590/s1677-5538.ibju.2015.0528
|View full text |Cite
|
Sign up to set email alerts
|

A prospective multicenter European study on flexible ureterorenoscopy for the management of renal stone

Abstract: Purpose The aim of this study was to describe the outcomes and the complications of retrograde intrarenal surgery (RIRS) for renal stones in a multi-institutional working group.Materials and Methods From 2012 to 2014, we conducted a prospective study including all RIRS performed for kidney stones in 4 European centers. Demographic information, disease characteristics, and perioperative and postoperative data were gathered. Patients and stone data, procedure characteristics, results and safety outcomes were ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 28 publications
(32 reference statements)
0
15
1
3
Order By: Relevance
“…The overall complication rate in the HD group was 21.1%, which is consistent with overall, nondensityspecific rates reported in the literature (8%-24.9%). 19,20 In this study, even though the intraoperative complication rate in the HD group was slightly higher than in the LD group, the difference was not statistically significant. The most common intraoperative complication in both groups was failure to reach the stone.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…The overall complication rate in the HD group was 21.1%, which is consistent with overall, nondensityspecific rates reported in the literature (8%-24.9%). 19,20 In this study, even though the intraoperative complication rate in the HD group was slightly higher than in the LD group, the difference was not statistically significant. The most common intraoperative complication in both groups was failure to reach the stone.…”
Section: Discussioncontrasting
confidence: 60%
“…The overall intraoperative complication rate in the HD group (8.8%) is also comparable to overall, nondensity-specific rates reported in the literature (7%-30%). 19,20 A single-center retrospective study reported that most intraoperative complications were minor, with insignificant clinical consequences. 21 This finding is in line with our results.…”
Section: Discussionmentioning
confidence: 99%
“…According to size, composition, and localization of the stone, stone-free rates vary from 65–100%. Complications occur in 0–20% 5, 45, 46, 48, 49 .…”
Section: Managing Urolithiasismentioning
confidence: 99%
“…1 Increased use of flexible ureterorenoscopy and holmium laser has made treatment possible of upper urinary system stones of various sizes with high stonefree rates, low morbidity, short hospital stay, and high patient comfort. 2 With these advantages, retrograde intrarenal surgery (RIRS) has become one of the most important current treatment options applied to upper urinary system stones <2 cm. 3 In the European Urology Association (EUA) guidelines, it is shown together with shockwave lithotripsy (SWL) as an alternative treatment to percutaneous nephrolithotomy (PNL) for stones >2 cm.…”
Section: Introductionmentioning
confidence: 99%
“…In selected cases with negative factors such as low success of SWL in lower pole stones, 4 the difficulty of applying SWL and PNL in obese patients, pregnancy or coagulopathy, RIRS has become the primary treatment choice for stones >2 cm. 2 Although the treatment area of RIRS has broadened to this extent and it is preferred in many centres because of the low morbidity rates, there are also complications of RIRS, which cannot be ignored. 5 The most frequently encountered complication of this procedure is postoperative infection and despite prophylactic antibiotic treatment, incidence has been reported in literature of 1.7-18.8%.…”
Section: Introductionmentioning
confidence: 99%